Supporting the SMME sector for sustainable growth and development- in the Northern Cape province - Packirisamy, Kuberin (Graduate School of Business (GSB), 2023)
Small and Medium Enterprises are critical for creating employment and alleviating poverty and inequality by driving inclusive, sustainable socio-economic development. Therefore, as a vital sector, SMEs can improve the regional Gross Domestic Product growth and development by adding value to the complete value chain processes, from the production of the resources to the processing and eventually reaching the different markets. Hence Small and Medium Enterprises should play a pivotal role in revitalising Northern Cape Province's economic growth and development. Thus, dynamic entrepreneurs are required to drive these processes effectively. Unfortunately, however, in South Africa and Northern Cape Province, the failure rate of SMEs is very high. This paper aims to identify the determinants that affect SME growth and development in the Northern Cape Province. Five determinants identified for this study were human capital, market capability, infrastructure and technology and entrepreneurial orientation. Cross-sectional survey data were collected via email among 128 SME owners/managers in the Northern Cape Province. The quantitative methodologies approach was built on the Partial Least Squares Structural Equation Model to analyse the model's reliability, and validity, by analysing the measurement model and hypothesis testing predictiveness by analysing the structural model utilising Smart PLS vers3 software. The empirical research results indicated the direct effects of a statistically positive effect of human capital, market capability, infrastructure and technology, and entrepreneurial orientation on SME growth and development. However, the direct effects between infrastructure and technology and SME growth and development are significantly negative. The indirect effects indicated that market capability as a mediator between entrepreneurial orientation and SME growth and development is positively significant. However, infrastructure and technology are negatively significant. The moderation effect of human capital was found to be positively significant. If human capital were not introduced as a moderator, the relationship between entrepreneurial orientation and SME growth and development would be insignificant, indicating the importance of human capital for SME growth and development. Human capital as a moderator would contribute to the Resource-Based View and assist in policy development to improve SME growth and developmen